REFLECTIONS ON MONETARISM: Britain's Vain Search for a Successful Economic Strategy - Tim Congdon (Edward Elgar Publishing, 1992)
The last 20 years have seen severe macroeconomic instability in Britain, with three extreme and highly damaging boom-bust cycles. Professor Tim Congdon, one of the City's most well-known commentators, has been an influential critic of successive governments' failures in economic policy throughout this period. Reflections on Monetarism brings together his most important academic papers and journalism, including his remarkably prescient series of articles in The Times from 1985 to 1988 forecasting that the Lawson credit boom would wreck the Thatcher Government's reputation for sound financial management. He presents a powerful argument that the root cause of Britain's economic instability has been the volatile growth of credit and the money supply.